Exploring How Albumin Supplementation Affects Serum Albumin Levels, CD8+ Lymphocyte Counts, and Interferon Gamma In Rifampicin-Resistant TB Patients - Yusdianto, Adrian; Chozin, Iin Noor; Sartono, Teguh Rahayu; Tantular, Rezki; Chilmi, Syahrul; Setijowati, Nanik (Jurnal Respirologi Indonesia, 2025)
Background: Drug-resistant tuberculosis (DR-TB) remains a global health threat, with increasing cases unresponsive to rifampicin therapy. Diagnosing rifampicin-resistant TB (RR-TB) requires a multidisciplinary approach, in which markers such as interferon-gamma (IFN-ɣ) are useful for diagnosis, monitoring, therapy evaluation, and prognosis. Hypoalbuminemia commonly accompanies TB patients, evidenced by weight loss and reduced serum albumin levels. TB infection stimulates cytokine production, which suppresses albumin synthesis and regulation, affecting both prognosis and treatment success, particularly in RR-TB. This study aimed to evaluate the role of albumin supplementation in improving serum albumin levels, CD8+ lymphocyte counts, and IFN-ɣ levels in RR-TB patients. Methods: This true experimental study with a pre- and post-test control group design was conducted at Saiful Anwar Hospital. Thirty subjects were recruited: 10 healthy individuals (control group), 10 RR-TB patients receiving albumin supplementation (egg white extract) for 30 days (RR-TB + Albumin), and 10 RR-TB patients without supplementation (RR-TB only). Peripheral blood samples were collected before and after anti-TB drug (ATD) and albumin administration. Flow cytometry was used for analysis. Data were analyzed using SPSS and Partial Least Squares (PLS) analysis. Results: Significant differences in albumin and IFN-ɣ levels were observed between the control and RR-TB groups before supplementation. No significant differences were found in CD8+ lymphocyte counts (P=0.402) or IFN-ɣ levels (P=0.390) between supplemented and non-supplemented RR-TB patients. However, albumin levels (P=0.003) and body weight (P=0.014) increased significantly in the supplemented group. Conclusion: Albumin supplementation significantly increases serum albumin levels and body weight in RR-TB patients, but does not significantly affect CD8+ lymphocyte counts or IFN-ɣ levels.